Analysis of accessible school uniforms for children with special needs - Baizhanova , Жазира; Madiyeva , Мадина (Рroblems of engineering and professional education, 2024)
This article examines the importance of designing and developing adaptive clothing for girls with autism spectrum disorder (ASD). Creating comfortable, safe, and functional school uniforms for such children is an increasingly relevant issue, as standard clothing models often fail to meet their unique needs. The study highlights the significance of adapting clothing elements—such as materials, fastenings, and construction—to reduce sensory discomfort, heightened tactile sensitivity, and challenges with independent dressing. Key attention is given to principles of inclusivity and ergonomics, ensuring freedom of movement and comfort. The article analyzes factors affecting fabric and design choices that contribute to improving the quality of life for children with ASD. Additionally, the study examines how adaptive school uniforms can impact children's self-esteem and confidence, providing a sense of belonging to the school community and reducing the stress of daily tasks. The influence of adaptive design on the development of self-care skills and motivation for independence is also considered, which is especially important for children with special needs who face challenges in communication and social adaptation. The findings of this study can assist designers and manufacturers in creating inclusive clothing that fosters children’s social adaptation and independence in self-care.